Cerdos - Brady, Peter, 1944 September 22- (Mankato, Minn. : Bridgestone Books, 1999)
Introduces pigs by describing their physical characteristics, where they live, what they eat, their special skills, and what they provide for people.
Includes bibliographical references (page 24) and index.
Espanol = Spanish.
Keywords: Swine -- Juvenile literature; Pigs; Spanish language materials; Juvenile works